MOLECULAR DOCKING STUDIES ON PENICILLIN-BINDING PROTEIN 3 OF STREPTOCOCCUS PNEUMONIA- HUNGARY 19A-6 STRAIN - BALASANKAR KARAVADI,; M. XAVIER SURESH, (International Journal of Pharma and Bio Sciences, 2014)
Streptococcus pneumoniae in human upper respiratory tract causes mucosal diseases. HUNGARY19A-6 strain of Streptococcus pneumoniae is extremely virulent in pneumococcal pathogenesis which contains Protein coding gene which synthesis Penicillin-binding protein 3. In this article we performed the homology modeling studies of the virulent protein which is synthesized by the protein coding gene and validated the nature of the receptor as a future drug target for HUNGARY19A-6 strain of Streptococcus pneumonia. We have also identified specific ligands for the above mentioned protein by using the virtual structure based ligand screening approach. Protein-ligand complexes have been analyzed by docking studies using Discovery Studio and interactions have also been visualized along with the validation of pharmacokinetic descriptors.